Differential expression of HIV target cells CCR5 and α4β7 in tissue resident memory CD4 T cells in endocervix during the menstrual cycle of HIV seronegative women - Govindaraj, Sakthivel; Tyree, Staple; Herring, Gina Bailey; Rahman, Sadia J.; Babu, Hemalatha; Ibegbu, Chris; Young, Marisa R.; Mehta, C. Christina; Haddad, Lisa B.; Smith, Alicia K.; Velu, Vijayakumar (Frontiers in Immunology, 2024)
Background: Ovarian hormones are known to modulate the immune system in the female genital tract (FGT). We sought to define the impact of the menstrual cycle on the mucosal HIV target cell levels, and tissue-resident CD4 T cells.Here, we characterized the distribution, phenotype, and function of CD4 T cells with special emphasis on HIV target cells (CCR5+ and α4β7+) as well as tissue-resident memory (TRM; CD69+ and CD103+) CD4 T cells in FGT of cycling women. Peripheral blood and Endocervical cells (EC-collected from cytobrush) were collected from 105 healthy women and performed multicolor flow cytometry to characterize the various subsets of CD4 T cells. Cervical vaginal lavage (CVL) were collected for cytokine analysis and plasma were collected for hormonal analysis. All parameters were compared between follicular and luteal phase of menstrual cycle.Our findings revealed no significant difference in the blood CD4 T cell subsets between the follicular and the luteal phase. However, in EC, the proportion of several cell types was higher in the follicular phase compared to the luteal phase of menstrual cycle, including CCR5+α4β7-cells (p=0.01), CD69+CD103+ TRM (p=0.02), CCR5+CD69+CD103+ TRM (p=0.001) and FoxP3+ CD4 T cells (p=0.0005). In contrast, α4β7+ CCR5-cells were higher in the luteal phase (p=0.0004) compared to the follicular phase. In addition, we also found that hormonal levels (P4/E2 ratio) and Th2 cytokines (IL-5 and IL-6) were with CCR5+ CD4 T cells subsets during the follicular phase of the menstrual cycle Conclusion: Overall, these findings suggest the difference in the expression of CCR5 and α4β7 in TRM CD4 T cell subsets in endocervix of HIV seronegative women between the follicular and luteal phase. Increase in the CCR5+ expression on TRM subsets could increase susceptibility to HIV infection during follicular phase of the menstrual cycle.